Spatial and diurnal distributions of n-alkanes and n-alkan-2-ones onPM(2.5) aerosols in the Lower Fraser Valley, Canada - Y. Cheng; Li, S. M.; Leithead, A.; Brook, J. R. (ATMOSPHERIC ENVIRONMENT, 2006)
Ninety daytime/nighttime PM2.5 aerosol samples were collected at 5 sites in forest, tunnel, urban, rural, and mixed forest/urban areas in the Lower Fraser Valley during the Pacific 2001 Air Quality Study. Solvent-extractable organic matter, such as n-alkanes (C-14-C-33), n-alkan-2-ones (C-10-C-31), and 6, 10, 14- trimethylpentadecan-2-one on the fine aerosols, were quantified. The concentrations of total n-alkanes from primary sources were 45.5-112 ng m(-3) at the tunnel site, 3.3-34.6 ng m(-3) at the urban site, 0.6-18.1 ng m-3 at the rural site, and 1.7-16.9 ng m(-3) at the forest and the mixed areas. The homologue distributions of the n-alkanes displayed different patterns at the 5 sites, showing day-night differences and reflecting their primary source types and impacts of episodes. The carbon preference index (CPI) values of the n-alkanes showed highest value (average of 2.39 +/- 0.47) at the forest, lowest (1.15 +/- 0.11) at the tunnel. The CPI showed higher values in night samples at all sites except the urban site which was impacted by specific episodes such as biomass burning and/or fuel burning occurring during the nighttimes, the higher nighttime values of CPI, with consistent lower n-alkane concentrations, suggested that weaker anthropogenic emissions during night were a more likely cause. The total n-alkan-2-ones on the aerosols were 1.8-12.6ng m(-3) at the tunnel site and 0.2-7.2ng m-3 at the other 4 sites. Low-molecular weight n-alkan-2-ones (< C-22) were observed at all sites with the highest level at the tunnel. High molecular weight n-alkan-2-one (> C-23) were consistently higher at the tunnel but varied with date at the forest site. The n-alkan-2ones, both low and high molecular weight, could have multiple sources including vehicular emissions and oxidation processes. The branched ketone, 6, 10, 14- trimethylpentadecan-2-one, an oxidative product of phytol on the fine aerosols, 3 was enriched in the forest with the average of 7.6 +/- 7.1 ng mg(-3) (c) 2006 Elsevier Ltd. All rights reserved.